2006
DOI: 10.1007/s11250-006-4426-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of production systems and selection criteria of Ankole cattle by breeders in Burundi, Rwanda, Tanzania and Uganda

Abstract: A survey in Burundi, Rwanda, Tanzania and Uganda was conducted in order to determine the different production systems under which Ankole cattle are currently kept. Additionally, selection criteria of livestock keepers were documented. In Burundi, Rwanda and parts of Uganda, livestock keepers are sedentary and herds are small, whereas in the other areas Ankole cattle are kept in large herds, some of them still under a (semi-)nomadic system. Milk is the main product in all areas, and is partly for home consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 8 publications
3
50
0
1
Order By: Relevance
“…These differences can be further accounted for by the particular indigenous selection criteria of the herd Genetic and morphological characterisation of the Ankole cattle owners from central Uganda and north-western Tanzania, who tend to emphasise aesthetic traits more than what the cattle owners of the other sub-populations do. These findings are also consistent with the observations made by Wurzinger et al [38], who found that appearance-related features such as coat colour and horns were ranked highly as selection criteria mainly in the Uganda Central and Kagera areas.…”
Section: Geometric Morphometric Descriptionsupporting
confidence: 92%
See 4 more Smart Citations
“…These differences can be further accounted for by the particular indigenous selection criteria of the herd Genetic and morphological characterisation of the Ankole cattle owners from central Uganda and north-western Tanzania, who tend to emphasise aesthetic traits more than what the cattle owners of the other sub-populations do. These findings are also consistent with the observations made by Wurzinger et al [38], who found that appearance-related features such as coat colour and horns were ranked highly as selection criteria mainly in the Uganda Central and Kagera areas.…”
Section: Geometric Morphometric Descriptionsupporting
confidence: 92%
“…Among the different ethnic groups in the study areas, morphological size traits and those of aesthetic value play different but equally important roles in the selection decisions made by herd owners. Indeed, aesthetic traits were highly ranked as selection criteria by the herd owners from the three central Ugandan sub-populations, as documented by Ndumu et al [22] and Wurzinger et al [38].…”
Section: Stepwise Discriminant Analysismentioning
confidence: 72%
See 3 more Smart Citations